2021
DOI: 10.1101/2021.07.16.21260657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Modeling shield immunity to reduce COVID-19 transmission in long-term care facilities

Abstract: Nursing homes and other long-term care facilities in the United States have experienced severe COVID-19 outbreaks and elevated mortality rates, often following upon the inadvertent introduction of SARS-CoV-2. Following FDA emergency use approval, widespread distribution of vaccines has resulted in rapid reduction in COVID-19 cases in vulnerable, older populations. Yet, vaccination coverage remains incomplete amongst residents and healthcare workers. As such, mitigation and prevention strategies are needed to r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In Germany, [35] studied COVID-19 outbreaks in retirement homes and found that symptom control and testing, in addition to vaccination, are effective prevention strategies. [36] employed an SEIR network epidemic model based on disease status. They used the model to study a shield-immunity approach, considering a bipartite network between the staff and residents.…”
Section: Related Workmentioning
confidence: 99%
“…In Germany, [35] studied COVID-19 outbreaks in retirement homes and found that symptom control and testing, in addition to vaccination, are effective prevention strategies. [36] employed an SEIR network epidemic model based on disease status. They used the model to study a shield-immunity approach, considering a bipartite network between the staff and residents.…”
Section: Related Workmentioning
confidence: 99%
“…The effect of a cyclic 4-day work and 10-day lockdown strategy in the workplace has been investigated by [27]. In nursing homes and long-term care facilities, [28] constructed a mathematical model based on bipartite networks consisting of health care workers and facility residents to investigate how restructuring interactions via the concept of shied immunity can change outbreak dynamics. Specifically, shield immunity refers to the practice of proportionally increasing the interactions between recovered and susceptible individuals to protect the susceptible from infection.…”
Section: Related Workmentioning
confidence: 99%
“…The effect of cyclic 4-day work and 10-day lockdown strategy in workplace has been investigated by [26]. In nursing home and long-term care facilities, [27] constructed a mathematical model based on bipartite network consists of health care workers and the residents and investigated how the restructured interactions in the bipartite network can change the outcome of the epidemics in the facility by exploiting the strategy of shied immunity, where the recovered people increase their interactions with susceptible population to protect them from the infection. In order to support the decision-making process, [28] developed a strategy to predict the risk of infection among the health workers and other employees in the essential sectors by taking into account the working process, proximity between employees, type of activity, etc.…”
Section: Introductionmentioning
confidence: 99%